PENDIDIKAN ANAK DI ERA DIGITAL: PERAN INOVASI DAN TEKNOLOGI DALAM MENGEMBANGKAN KECERDASAN ABAD 21 - Ahmad Tamyiz; Bibin Siti Milaturahmah; Citra Eka Wulandari; Dessy Kurnia Mulyani; Fauzan Akmal Firdaus (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
The digital revolution has presented challenges in the child education system, including gaps in access to digital infrastructure, limitations in teachers' competence in integrating technology, and concerns about negative impacts on children's socio-emotional development. This study aims to analyze the role of innovation and technology in education in the digital era, explore effective technology-based learning models, and identify strategies for developing children's intelligence to meet the demands of the 21st century. The method used was a systematic literature review with a thematic analysis of peer-reviewed journals from leading academic databases. The results show that technology plays a significant role in creating personal, collaborative, and inclusive learning through game-based learning, adaptive learning, and artificial intelligence-based applications. The effectiveness of technology integration depends on a blended learning approach, adequate infrastructure, educator training, and policies that support equitable access, thus requiring stakeholder collaboration in creating an optimal digital education ecosystem. Keywords: digital learning, 21st century intelligence, educational innovation, technology gap